LEVERS OF CONTROL DAN KEUNGGULAN BERSAING: APAKAH PENGENDALIAN MANAJEMEN SEBUAH SISTEM? - Agnes Utari Widyaningdyah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
This study investigates the effect of Levers of Control (LoC) on competitive advantage with business environmental uncertainty as an antecedent variable. LoC as a form of company capability in facing environmental uncertainty is a source of company competitive advantage. Based on the resource-based theory, this research was conducted against the background of the decline in competitiveness of manufacturing companies in Indonesia during 2013-2018. The model of using LoC as a system outperforms the model of using LoC as a package to overcome business environmental uncertainty and to improve the companies’ competitive advantage. As a system, the LoC has interplay between the levers so that it can be of full use in realizing a competitive advantage.Levers of Control (LoC); Competitive Advantage; Business Environmental Uncertainty; Resource-based View